Customer Loyalty in Village-Owned Enterprises: The Effects of Product Innovation, Marketing Communication, and Price - Ida Ayu Sintha Agustina; I Gusti Ayu Meta Purmina Dewi; I Komang Oka Permadi (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2026)
This study aims to analyze how product innovation, marketing communication, and price influence customer loyalty toward the Tri Bhuana Kerthi BUMDes in Tegaljadi Village, Marga Subdistrict, Tabanan Regency. The study employs a quantitative, causal-associative design approach. Data were collected via a questionnaire distributed to 125 randomly selected customers. Data analysis was conducted through instrument validation, classical assumption tests, multiple linear regression, the coefficient of determination, and partial and simultaneous hypothesis testing. The results indicate that product innovation has not yet significantly affected customer loyalty. However, marketing communication and price were found to positively and significantly affect customer loyalty. Additionally, product innovation, marketing communication, and price were found to have a significant effect on customer loyalty. These findings confirm that customer loyalty to BUMDes is more strongly shaped by effective marketing communication and appropriate price perceptions than by product innovation alone. Therefore, managers need to strengthen communication strategies, maintain affordability, and direct product innovation toward customers' real needs.